2014
DOI: 10.3168/jds.2014-7961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfalfa and cereal straw as a forage source on nutrient digestibility and lactation performance in lactating dairy cows

Abstract: This study was conducted to investigate the nutrient digestibility and lactation performance when alfalfa was replaced with rice straw or corn stover in the diet of lactating cows. Forty-five multiparous Holstein dairy cows were blocked based on days in milk (164 ± 24.8 d; mean ± standard deviation) and milk yield (29.7 ± 4.7 kg; mean ± standard deviation) and were randomly assigned to 1 of 3 treatments. Diets were isonitrogenous, with a forage-to-concentrate ratio of 45:55 [dry matter (DM) basis] and containe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(148 citation statements)
references
References 34 publications
11
127
5
1
Order By: Relevance
“…An increase in digestibility of DM and OM when diets are supplemented with SFC rather than GC has also been reported (Cooke et al, 2009), as has the fact that feed intake was reduced with lowered digestibility of DM (Faverdin et al, 1999). Moreover, with a diet high in digestible energy, the energy intake ceased to increase with ration digestibility (Conrad et al, 1964;Wang et al, 2014). In the current study, HE diets increased the total-tract digestibility of DM, OM, CP, NDF, ADF, and starch, but no such differences were observed between the HE/GC-and HE/SFC-based diets.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…An increase in digestibility of DM and OM when diets are supplemented with SFC rather than GC has also been reported (Cooke et al, 2009), as has the fact that feed intake was reduced with lowered digestibility of DM (Faverdin et al, 1999). Moreover, with a diet high in digestible energy, the energy intake ceased to increase with ration digestibility (Conrad et al, 1964;Wang et al, 2014). In the current study, HE diets increased the total-tract digestibility of DM, OM, CP, NDF, ADF, and starch, but no such differences were observed between the HE/GC-and HE/SFC-based diets.…”
mentioning
confidence: 72%
“…In the present study, both MCP and IADP values were higher in cows fed HE diets, which we propose are associated with greater MP supply and milk protein yield. Previous research has shown that a greater concentration of dietary NFC is positively correlated with MCP yield (Nocek and Russell, 1988;Lascano and Heinrichs, 2011;Wang et al, 2014). In the HE diets, in contrast to the LE diets, CS was replaced with corn silage, thereby increasing the dietary energy level and improving DMI.…”
Section: Rumen Degradation and Estimated Mcp Yieldmentioning
confidence: 96%
See 2 more Smart Citations
“…Forage quality greatly affects dairy cow performance [1, 2]. Using traditional nutritional methods, it is difficult to discern metabolic alterations and characterize alterations in key metabolic pathways when dairy cows are fed diets differing in forage quality.…”
Section: Introductionmentioning
confidence: 99%